Inflammation associated with chronic heart failure leads to enhanced susceptibility to depression. (19th April 2019) - Su, Jing; Wang, Jinghui; Ma, Yuanyuan; Li, Qing; Yang, Yufang; Huang, Li; Wang, Haoyue; Li, Heng; Wang, Zishan; Tong, Jiabin; Huang, Dongping; Bai, Xiaochen; et al.
Abstract : Epidemiological and clinicopathological studies indicate that there is a high risk for chronic heart failure (CHF) in patients suffering from neuropsychiatric disorders, such as depression. However, it is unclear whether CHF causes depression, and the underlying mechanisms of this association remain largely unknown. In this study, mice with myocardial infarction and CHF were used to investigate behavioral alterations as well as changes in the brain‐heart axis. During the first 6 months, abnormalities in neuropsychiatric behaviors were detected in mice with CHF. Using the sucrose preference test, a 9 months course of CHF resulted in two subgroups: mice with a significant decrease in sucrose preference, defined herein as "susceptible" (Sus), and mice with a normal sucrose preference, defined herein as "resilient." Compared to the resilient and sham‐operated animals, the Sus mice displayed imbalances in glutamate transmission and hypothalamic–pituitary–adrenal axis activation, abnormal synaptic plasticity, and increased inflammatory responses. Furthermore, abnormal kynurenine metabolism was detected in Sus mice. Our results suggest that long‐term CHF increases inflammatory responses in the central nervous system and leads to depression in Sus mice. Abstract : Mice with chronic heart failure (CHF) were used to investigate behavioral alterations and changes in the brain‐heart axis. A 9 months course of CHF resulted in two subgroups: "susceptible" mice with a significant decrease in sucrose preference, and "resilient" mice with a normal sucrose preference. Compared to resilient and sham‐operated animals, susceptible mice displayed imbalances in glutamate transmission and hypothalamic–pituitary–adrenal axis activation, abnormal synaptic plasticity, increased inflammatory responses and abnormal kynurenine metabolism.